A new Rakaia species (Opiliones, Cyphophthalmi, Pettalidae) from Otago, New Zealand - Boyer, Sarah L.; Giribet, Gonzalo (Zootaxa, 2003)
Rakaia macra sp. nov. is described from three lots of specimens collected by Ray Forster in 1977 from Waipori, Otago, South Island of New Zealand. This species is currently known only from the Waipori area (exact locality unspecified) where it is extremely abundant. Clearly a member of the family Pettalidae, R. macra sp. nov. presents unusual chelicerae, with a conspicuous outer lateral ridge on the second segment, and without the two types of denticles in the mobile digit that characterize the New Zealand pettalids. The relationships between the new species and its closest relatives are discussed, and the distinction between the genera Rakaia and Neopurcellia is questioned.